Vestibular Migraine in an Otolaryngology Clinic: Prevalence, Associated Symptoms, and Prophylactic Medication Effectiveness. Issue 1 (January 2015) - Van Ombergen, Angelique; Van Rompaey, Vincent; Van de Heyning, Paul; Wuyts, Floris
Abstract : Objective: To assess the prevalence of vestibular migraine (VM) in patients consulting to an otolaryngology clinic, the neuro-otological associated symptoms, and the effect of prophylactic antimigrainous medication on VM symptom improvement. Study Design: Retrospective chart review. Setting: Tertiary referral otolaryngology clinic. Subjects and Methods: We used the diagnostic criteria from the Bárány Society and the International Headache Society to allocate patients to a subgroup: VM, possible VM, and atypical VM. Main Outcome Measure: The prevalence of VM, percentages of associated neurotological symptoms, and percentages of effectiveness of prophylactic medication. Results: Sixty-five (16%) patients were selected from the total patient population (n = 407) from which 4.2% were assigned to the definite VM group, 5.7% to the probable VM group, and 6.1% to the atypical VM group. We found a significantly different distribution between the groups for photophobia ( p = 0.035), ear pressure ( p = 0.023), and scotoma ( p = 0.015). Thirty patients were administered with flunarizine and 68% responded with an improvement in VM symptoms ( p < 0.001). For propranolol, 31 patients were treated and there was an improvement of symptoms in 73% ( p < 0.001). Remarkable was the fact that these percentages were not significantly different between the subgroups. Conclusion: VM is a common disorder presenting in a dizziness clinic, and detailed history taking is important to assess VM-associated symptoms and thus to prevent underdiagnosis. The latter is very important because our study shows that the majority of patients, regardless of VM subtype, can benefit from a prophylactic treatment, but further prospective studies are necessary.